Forest of a thousand lanterns - Dao, Julie C. (Dao, Julie C. Rise of the empress, 2017)
Beautiful eighteen-year-old Xifeng, raised by a cruel aunt who says the stars destine her to be Empress of Feng Lu, chooses to spurn the man who loves her and exploit the dark magic that can make her dream real.